Impact of loss‐of‐function mutations at the RNF43 locus on colorectal cancer development and progression. Issue 4 (20th June 2018) - Eto, Tsugio; Miyake, Keisuke; Nosho, Katsuhiko; Ohmuraya, Masaki; Imamura, Yu; Arima, Kota; Kanno, Shinichi; Fu, Lingfeng; Kiyozumi, Yuki; Izumi, Daisuke; Sugihara, Hidetaka; Hiyoshi, Yukiharu; et al.
Abstract: RNF43 mutations are frequently detected in colorectal cancer cells and lead to a loss of function of the ubiquitin E3 ligase. Here, we investigated the clinical significance of RNF43 mutations in a large Japanese cohort and the role of RNF43 at various stages of colorectal cancer development and progression. Mutation analysis of the RNF43 gene locus with pyrosequencing technology detected RNF43 hotspot mutations in one (0.88%) of 113 colorectal polyp cases and in 30 (6.45%) of 465 colorectal cancer cases. Moreover, patients with colorectal cancer harbouring mutated RNF43 experienced a higher recurrence rate than those harbouring non‐mutated RNF43 . In addition, the growth of RNF43 wild‐type colorectal cancer cell lines was significantly increased by RNF43 silencing. We generated Rnf43 knockout mice in a C57BL/6 N background by using the CRISPR–Cas9 system. Although intestinal organoids from Rnf43 knockout mice did not show continuous growth in the absence of R‐spondin, an azoxymethane/dextran sodium sulphate mouse model demonstrated that tumours were markedly larger in Rnf43 knockout mice than in wild‐type mice. These findings provide evidence that Wnt signalling activation by RNF43 mutations during the tumourigenic stage enhances tumour growth and promotes a high recurrence rate in colorectal cancer patients. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.